Kerangka Hukum Aktifasi Warisan Tambang Batu Bara Ombilin Sawahlunto dan Jalur Kereta Api - Simabura, Charles (Universitas Andalas, 2024)
The Ombilin Sawahlunto Coal Mine World Heritage management requires a strong legal basis to guide the parties involved. This is because multiple parties, such as local governments, central governments, BUMN, and community ownership, own various world heritage sites, objects, and properties. The legal study in this paper presents the results of mapping the legislation, authority, ownership, and challenges in its management by the Management Agency that needs to be formed. With a strong legal basis, it will be able to support various steps in managing this world heritage in the future.